Optimalisasi Program Mangrove Literacy Edutourism (MANGLIEDS) Berbasis Konservasi Mangrove - Guntur, Mochamad; Hasanah, Dede; Musyarrofah, Siti; Ningsih, Nur Indah Septia; Sahronih, Siti (Program Studi Pendidikan Guru Sekolah Dasar Universitas Flores Ende, 2023)
Mundupesisir Village is one of the potential villages located on the coast of West Java due to the presence of mangrove conservation along its shores. Mangroves are crucial ecosystems for environmental enhancement, but in reality, this conservation effort has received less intensive attention. Therefore, a strategy is needed to develop and enhance environmental awareness through the improvement of literacy. MANGLIEDS is an edutourism-based mangrove literacy enhancement program initiated to address this issue. The development of literacy in Mundupesisir Village utilizes Participatory Rural Appraisal (PRA) as a method for planning, implementation, monitoring, and evaluation. This approach encourages active participation of the community at all levels, directing development towards their needs and aspirations, enhancing their involvement, and facilitating program implementation. The MANGLIEDS program includes strengthening student involvement, community empowerment, collaboration with the village government, and project management, providing a comprehensive approach to promote understanding and awareness of the importance of mangrove forests. Through socialization activities, training, and the development of mangrove edutourism ventures, this program can enhance the community's knowledge of the ecological and economic benefits of mangrove forests and inspire awareness of their conservation. This program not only benefits the local community but also provides opportunities for students to develop their skills and knowledge in the field of environment and sustainability. Thus, MANGLIEDS can serve as an inspirational and effective model in integrating edutourism and mangrove literacy into a cohesive entity that positively impacts environmental preservation and the well-being of the local community.